PROFIL GAYA BELAJAR PESERTA DIDIK KELAS X DI SMA ADABIAH 2 PADANG - Neksi, Lenda Putri (Bimbingan dan Konseling, 2014)
The research looked at the phenomenon of persistence of students who do not understandtheir learning styles in learning. This study aims to describe 1) visual learning styles, 2) auditorylearning style, 3) kinesthetic learning styles.The population in this study was tenth grade studentsof SMA Adabiah 2 Padang. Population are 281 people. The selected based on simple randomsampling technique. Samples are 74 people. Sources of data in this study are primary andsecondary. Technique of data collection is questionnaire and then processed using percentagetechniques.The results of this study revealed that the general profile learning styles of students intenth grade students of SMA Adabiah 2 Padang is on many criteria. Seen from each sub variabel:1). Visual learning styles is on many criteria, 2). Auditory learning styles is on many criteria, 3).Kinesthetic learning styles is on many criteria.